Biotechnological approaches in glucosinolate production. Issue 12 (1st October 2018) - Petersen, Annette; Wang, Cuiwei; Crocoll, Christoph; Halkier, Barbara Ann
Abstract: Glucosinolates (GLSs) are sulfur‐rich, amino acid‐derived defense compounds characteristic of the Brassicales order. In the past, GLSs were mostly known as anti‐nutritional factors in fodder, biopesticides in agriculture, and flavors in condiments such as mustard. However, in recent times, GLSs have received increased attention as promoters of human health. This has spurred intensive research towards generating rich sources of health‐promoting GLSs. We provide a comprehensive overview of the biotechnological approaches applied to reach this goal. This includes optimization of GLS production and composition in native, GLS‐producing plants, including hairy root and cell cultures thereof, as well as synthetic biology approaches in heterologous hosts, such as tobacco and the microbial organisms Escherichia coli and Saccharomyces cerevisiae . The progress using these different approaches is discussed. Abstract : This review provides a comprehensive overview of the biotechnological approaches to generate rich sources of health‐promoting glucosinolates, including comparison of glucosinolate production levels in hairy root and cell cultures of brassicaceous plants, in heterologousplant hosts like tobacco, and in the microorganisms Escherichia coli and Saccharomyces cerevisiae .